Static and Short-Circuit Performance Analysis of the 4H-SiC 3.3 kV Trench Semi-SJ MOSFET - Melnyk, Kyrylo; Renz, Arne B.; Kotagama, Virendra; Cao, Qinze; Iosifidis, Nikolaos; Gammon, Peter M.; Gott, James A.; Shah, Vishal A.; Lophitis, Neophytos; Rahimo, Munaf; Nistor, Iulian; Maresca, Luca; et al. (My University, 2025)
This study investigates the static and Short-Circuit performance of a 3.3 kV semi-Superjunction (SJ) MOSFET using TCAD simulations, benchmarked against a fabricated conventional planar MOSFET. The proposed design is based on the cost-effective trench etching and side-wall implantation fabrication method. The analysis demonstrates a wide implantation window, defined by SC withstand time (SCWT) and maximum blocking voltage (BV) performance. Compared to the fabricated MOSFET, the proposed semi-SJ design achieves a 22% improvement in on-state resistance (Ron) and an 11% increase in maximum BV.
Keywords: 4H-SiC; MOSFET; Trench; Superjunction; ShortCircuit; High voltage device; Robustness; TCAD simulation